COMBINED PARS PLANA VITRECTOMY AND SCLERAL FIXATION OF AN INTRAOCULAR LENS USING GORE-TEX SUTURE: One-Year Outcomes. Issue 7 (July 2018) - Khan, M. Ali; Samara, Wasim A.; Gerstenblith, Adam T.; Chiang, Allen; Mehta, Sonia; Garg, Sunir J.; Hsu, Jason; Gupta, Omesh P.
Abstract : Purpose: To report the 1-year clinical outcomes of combined pars plana vitrectomy and ab externo scleral fixation of an intraocular lens using Gore-Tex suture. Methods: Retrospective, interventional case series. Outcome measures were change in visual acuity and occurrence of intraoperative and postoperative complications with minimum follow-up of 1 year. Results: Eighty-four eyes of 83 patients were identified. The mean best available visual acuity improved from 20/782 preoperatively to 20/65 postoperatively ( P < 0.001). The mean follow-up was 598 ± 183 days (median 533 days, range 365–1, 323 days). There were no intraoperative complications noted. A Bausch & Lomb Akreos AO60 intraocular lens was implanted in 77 eyes and an Alcon CZ70BD in 7 eyes. Postoperative complications included transient vitreous hemorrhage in six eyes (7.1%), cystoid macular edema in four eyes (4.8%), ocular hypertension in three eyes (3.6%), hyphema in two eyes (2.4%), and transient corneal edema in two eyes (2.4%). There were no cases of postoperative endophthalmitis, suture erosion/breakage, hypotony, retinal detachment, suprachoroidal hemorrhage, choroidal detachment, uveitis–glaucoma–hyphema syndrome, or persistent postoperative inflammation during the follow-up period. Conclusion: Combined pars plana vitrectomy and ab externo scleral fixation of an intraocular lens with Gore-Tex suture was well tolerated at a minimum of 1-year follow-up. No suture-related complications were encountered. Abstract : Supplemental Digital Content is Available in the Text.The authors describe 1-year outcomes of combined pars plana vitrectomy and scleral fixation of an intraocular lens using Gore-Tex suture. Combined surgery demonstrated significant visual improvement with low rates of intraoperative and postoperative complications. Long-term outcomes revealed stable intraocular lens placement without suture-related complications.